Galleria mellonella: A Novel Invertebrate Model to Distinguish Intestinal Symbionts From Pathobionts - Lange, Anna; Schäfer, Andrea; Bender, Annika; Steimle, Alexander; Beier, Sina; Parusel, Raphael; Frick, Julia-Stefanie (Frontiers in Immunology, 2018)
Insects and mammals share evolutionary conserved innate immune responses to maintain intestinal homeostasis. We investigated whether the larvae of the greater wax moth Galleria mellonella may be used as an experimental organism to distinguish between symbiotic Bacteroides vulgatus and pathobiotic Escherichia coli, which are mammalian intestinal commensals. Oral application of the symbiont or pathobiont to G. mellonella resulted in clearly distinguishable innate immune responses that could be verified by analyzing similar innate immune components in mice in vivo and in vitro. The differential innate immune responses were initiated by the recognition of bacterial components via pattern recognition receptors. The pathobiont detection resulted in increased expression of reactive oxygen and nitrogen species related genes as well as antimicrobial peptide gene expression. In contrast, the treatment/application with symbiotic bacteria led to weakened immune responses in both mammalian and insect models. As symbionts and pathobionts play a crucial role in development of inflammatory bowel diseases, we hence suggest G. mellonella as a future replacement organism in inflammatory bowel disease research.